Prevalence Of Coronary Artery Disease and Its Association with Various Risk Factors in Rural Area of Nagpur - Sinha, Umesh; Bhardwaj, Sumit Dutt (National Journal of Community Medicine, 2016)
Introduction: Several factors appear likely to have contributed to the acceleration of CHD epidemic in India like demographic transition to an older population, as a result of increasing life expectancy and confluence of both conventional risk factors and non-conventional risk factors in Indians. Material and methods: It was a cross-sectional study, carried out in three villages of a PHC. A total of 3771 study subjects aged 15 years and above were included in the study. It was conducted from July 2007 to December 2009. We examined the prevalence of CHD using WHO Rose Angina questionnaire and various risk factors of NCDs in central part of India using the WHO STEP approach. Results: Prevalence of Coronary heart disease (affirmative response to ROSE questionnaire) among the study subject was 226 (6.0 %). In males it was 123 (6.3 %) while in females it was 103 (5.7 %). This difference was not found to be statistically significant (c2=0.529, df=1, P= 0.467). Conclusion: Risk factors for coronary heart disease which were higher among males were Smoking, smokeless tobacco and alcohol consumption. While hypertension, Obesity (BMI≥25kg/m2), sedentary type of physical activity, low fruits and vegetable consumption were the risk factors which were higher among females.